PENDAMPINGAN DIGITALISASI SISTEM PENGELOLAAN STOK KENDARAAN BERBASIS SPREADSHEET DI PT ERA TRANS - Syahroni, Nabila Elvina Putri; Evanthi, Ayundha (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This community service activity aims to improve the effectiveness of vehicle stock management at PT Era Trans Surabaya through the implementation of a digital system based on Google Spreadsheet. The method used is a participatory approach consisting of three stages: observation of the manual system, assistance in implementing the digital system, and evaluation of its effectiveness. The results show that the Spreadsheet-based system successfully increased recording efficiency, reduced input errors, and accelerated real-time data updates. In addition, administrative staff were able to operate the system independently after the assistance, and coordination among staff became more optimal. Overall, the implementation of this system contributes to improving administrative performance and supports digital transformation in the company’s vehicle inventory management.